Working in a Physically Dangerous Work Environment: Employee Vitality and Sustainable Behavior - Jahanshahi, Asghar Afshar; Brem, Alexander; Gholami, Hussain (Sustainability, 2019)
There is a limited understanding of the antecedents and consequences of employee vitality during war zone exposure. The current study is one of the first ones to investigate the direct effects of perceived danger on employee vitality by collecting data from Afghanistan, one of the most dangerous countries in the world. Furthermore, it was investigated how employee vitality affects sustainable behavior at the workplace. The hypotheses of the study have been tested by using data from two surveys collected from 192 employees working in small-sized private businesses in Afghanistan. The results indicate that high levels of perceived danger negatively impact employee vitality at work. In addition, we found that employees with vitality engage in more pro-environmental behavior in the workplace. The engagement of vital employees in pro-environmental behavior is higher among those employees who have a high level of environmental awareness. This paper concludes by presenting the limitations and implications of this study, as well as highlighting potential avenues for future research.<br
Keywords: perceived danger; employees’ vitality; sustainable behavior; Afghanistan; environmental awareness; war zone; sustainability